Live Vaccines Have Different NK Cells and Neutrophils Requirements for the Development of a Protective Immune Response Against Tuberculosis - Junqueira-Kipnis, Ana Paula; Trentini, Monalisa Martins; Marques Neto, Lázaro Moreira; Kipnis, André (Frontiers in Immunology, 2020)
It has been shown that neutrophils drive NK cells to activate DCs while NK cells regulate neutrophils survival. In response to mycobacteria, NK cells proliferate and produces IFN-γ, that appears to regulate the neutrophilic inflammatory responses to both M. tuberculosis infection and BCG vaccination. Although the role of neutrophils in the immune response to tuberculosis is a matter of debate, neutrophils were shown to be crucial to induce specific response against mc2-CMX vaccine. The objective of this study was to investigate the interplay between NK cells and neutrophils in regard to the development of a protective immune response against M. tuberculosis. Depletion of NK cells during vaccination did not alter the total number of neutrophils or DCs, but reduced the number of activated DCs, thus reducing the generation of Th1 specific immune responses and the protection conferred by mc2-CMX and BCG vaccines. However, only in mc2-CMX vaccination that neutrophil depletion interfered with the NK cell numbers and protection. In conclusion, it was shown that only when both NK and neutrophils were present, specific Th1 response and protection was achieved by mc2-CMX vaccine, while neutrophils although activated upon BCG vaccination were not necessary for the induced protection.